THE TOURISM DESTINATION COMPETITIVENESS: USING THE PROMETHEE GAIA MODEL (JURNAL ECONOMICA : Research of Economic And Economic Education, 2020)
The focus of this research's attention is how to rank the competitiveness of West Sumatra tourist destinations by using aspects of 3A2P, which tourist destinations have advantages and what design policies should be done. Research was conducted on nine main destinations. The study uses the promethee ranking method, sensitivity analysis and GAIA plane analysis. The results showed that the competitiveness of West Sumatra tourist destinations is determined by the aspects of promotion and accessibility aspects, but the aspects of amenity and attractiveness have not yet been successfully addressed, so that promotions carried out in general have made return visits low and many problems have disrupted the beauty, comfort, safety and even environmental damage, due to the promotion of tourism that has not been accompanied by the provision of amenities in the tourist destination. There are three tourist destination areas that have advantages in 3A2P aspects in West Sumatra namely Padang City, Bukittinggi City and Sawahlunto City. Factors causing its superiority are mainly on promotion and accessibility factors, but in the aspect of security and attractiveness almost all tourist destinations still experience a number of shortcomings of some of the criteria. The policy of increasing the main competitiveness of tourism in West Sumatra can be done most urgently (necessary conditions) is to improve the crystalline amenities and aspects of attractiveness. While the aspects of promotion and accessibility can be a second alternative (sufficient condition).